Driving Civil Servants Performance through Work Discipline, Organizational Culture, and Internal Communication - Kelsum, Ulmi; Hikmah, Khoirul (Strata Social and Humanities Studies, 2025)
In the era of bureaucratic reform and digital transformation, optimizing civil servant performance is critical for public sector effectiveness. This study examines the influence of work discipline, organizational culture, and internal communication on employee performance at the Regional Manpower and Transmigration Office of Yogyakarta (Disnakertrans DIY), Indonesia. A quantitative approach was employed, with data collected via Likert-scale questionnaires from 77 civil servants. Validity and reliability tests (Pearson Correlation, Cronbach’s Alpha > 0.60) ensured instrument robustness. Multiple linear regression analysis (SPSS 26) revealed that all three variables significantly enhance performance, both individually and collectively (p < 0.05). Organizational culture exhibited the strongest impact (β = 0.483), followed by work discipline (β = 0.254) and internal communication (β = 0.241). The F-test confirmed their synergistic effect (F-statistic = 110.394, p = 0.000). These findings align with global studies on public sector performance but offer novel empirical evidence from a developing bureaucratic context. The study recommends prioritizing cultural reinforcement, disciplinary compliance, and transparent communication channels to elevate performance. It contributes to public management literature by validating a tri-factor performance model and provides actionable insights for policymakers to align HR strategies with Indonesia’s akhlak values (Civil Servant Core Ethics).